2008
DOI: 10.1080/08958370801905524
|View full text |Cite
|
Sign up to set email alerts
|

Low Level of Exposure to Pesticides Leads to Lung Dysfunction in Occupationally Exposed Subjects

Abstract: Pesticides may contribute to adverse respiratory health effects among farmers and have been considered one causal factor for the rise in asthma prevalence. This cross-sectional study was conducted to evaluate potential respiratory function abnormalities following long-term pesticide exposure by means of a complete pulmonary function testing, including spirometry, lung volumes, and diffusing capacity for carbon monoxide. The study population was comprised by workers from a prominent intensive agriculture area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 32 publications
6
56
1
4
Order By: Relevance
“…Among pesticide applicators, several studies showed impairments in respiratory function, especially with paraquat (reduction associated with the number of years of application) [48] and organophosphate, carbamate, neonicotinoid insecticides and bipyridylium herbicides, sometimes with a dose-effect relationship [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among pesticide applicators, several studies showed impairments in respiratory function, especially with paraquat (reduction associated with the number of years of application) [48] and organophosphate, carbamate, neonicotinoid insecticides and bipyridylium herbicides, sometimes with a dose-effect relationship [46].…”
Section: Discussionmentioning
confidence: 99%
“…Working in the agricultural sector was assumed to be equivalent to being exposed to pesticides. However, although only a few studies assessed lifelong pesticide use and calculated cumulative exposure indexes, they all found a dose-effect relationship [32,37,46,48]. Table 2 presents a summary of the longitudinal studies on respiratory health and occupational pesticide exposure.…”
Section: Studies On Agricultural Workersmentioning
confidence: 99%
“…Hernandez menemukan bahwa dari 89 penyemprot dengan paparan herbisida bipyridilium mengalami penurunan kapasitas difusi paru, dan bahwa paparan terhadap insektisida neonicotinoid terkait dengan penurunan volume paru (kapasitas total paru, volume residu, dan kapasitas fungsional residu). 13 Keterkaitan detail riwayat keterpaparan pestisida terhadap perkembangan penyakit atau derajat keparahan gangguan pernafasan yang dialami petani, salah satunya terhadap PPOK belum terjawab dengan pasti. Oleh karena itu penelitian ini bertujuan menganalisis pengaruh aspek teknik aplikasi pestisida terhadap derajat keparahan PPOK pada petani guna mendukung upaya preventif.…”
Section: Pendahuluanunclassified
“…Although the acute toxic effects resulting from pesticide exposure are easily recognized in these subjects, the effects resulting from long-term exposure to low doses are often difficult to assess (3,4). Several studies have reported associations between exposure to agricultural chemicals and various deleterious health outcomes, including effects on the immune, hematological, nervous, endocrine and reproductive systems (5)(6)(7). These compounds have also been associated with DNA damage in human populations (8,9), various types of cancer (10)(11)(12)(13)(14) and degenerative diseases (15).…”
Section: Introductionmentioning
confidence: 99%